'Labour class' children in Indian classrooms: theorizing urban poverty and schooling. Issue 1 (2nd January 2022) - Yunus, Reva
Abstract: This paper challenges (inter)national development narratives that propose schooling as a way out of poverty in the global South by interrogating poor children's experience of pedagogic and disciplinary processes in an Indian classroom. It also develops a theoretical framework to interrogate the relationship between urban poverty and classroom processes which attends to wider class and caste relations in the contemporary context of economic liberalism and 'political and social illiberalism'. Drawing upon parent interviews and ethnographic fieldnotes from a classroom in a state school it unpacks the term, 'labour class', used by teachers to refer to pupils' social background. Further, deploying the notion of 'deficit view' it shows how pedagogic practice, physical and verbal aggression experienced by pupils and pupils' struggles to engage with classroom teaching are shaped by realities of deeply stratified schooling, inadequate infrastructure in state schools and the relationship between 'labour class' communities and middle-class teachers.